(untitled) (Bangladesh Journal of Pharmacology, 2013)
Methanol extracts of the roots of B. brevissima and B. parkeriana were examined for antidiabetic and antimicrobial activities. Six compounds i.e berberine, 8-oxo-berberine, dehydrocheilanthifoline, columbamine, jatrorrhizine and gluta-mic acid were isolated from the active fractions of these species for the first time. The antidiabetic activity was determined against Protein Tyrosine Phosphatase 1B (PTP 1B), a negative insulin regulator while the antimicrobial activity was performed against four bacterial strains: Mycobacterium marinum ATCC BAA535, sporadic Methicillin Resistant Staphylococcus aureus (SMRSA), endemic Methicillin Resistant Staphylococcus aureus (EMRSA) and Escherichia coli ATCC.8739 at different concentrations. Amongst the isolated compounds 8-oxo-berberine was found to be the most active antidiabetic (29 % of the positive control) while jatrorrhizine was the most active and selective antimicrobial against SMRSA and EMRSA (-1.2% of the DMSO (D) control).